Gum katira-silver nanoparticle-based bionanocomposite for the removal of methyl red dye - Saruchi; Kumar, Vaneet; Bhatt, Diksha; El-Serehy, Hamed A.; Pandey, Sadanand (Frontiers in Chemistry, 2023)
The present study aimed to synthesize gum katira-silver nanoparticle-based bionanocomposite. Different characterization techniques were used to analyze the synthesized bionanocomposite, such as Fourier transform infrared (FTIR) spectroscopy, field emission scanning electron microscopy (FESEM), thermo-gravimetric analysis (TGA), and transmission electronic microscopy (TEM). AgNPs were formed and were 6–20 nm in size. Thermo-gravimetric analysis showed that synthesized nanocomposites are more thermally stable than gum katira. All the reaction conditions, such as time, temperature, pH, solvent, amount of nanoparticles, the concentration of the initiator, crosslinker, and monomer were optimized with respect to swelling. The results showed that the highest percentage swelling (Ps) of Gk-cl-poly(AA) was 796%, and 867% of AgNPs were imbibed by Gk-cl-poly(acrylic acid)-AgNPs. Synthesized bionanocomposite was used as an adsorbent material for the adsorption of methyl red (MR) dye. The effects of different reaction conditions were also optimized to attain maximum adsorption of MR dye. The maximum dye adsorption through Gk-cl-poly(AA)-AgNPs bionanocomposite was 95.7%. Diverse kinetic and isotherm models were used to study the adsorption data. The R2 value was established as 0.987 and k2 was .02671. The greater R2 value of second-order kinetics over first-order kinetics suggested that MR adsorption by nanocomposite is best explained by pseudo-second-order kinetics, indicating that dye adsorption occurred through chemisorption. The R2 value was determined to be .9954. The correlation coefficient values of Gk-cl-poly(AA)-AgNPs were best fitted by the Freundlich adsorption isotherm. Overall, synthesized bionanocomposite is a proficient material for removing of MR dye from wastewater.